2009
DOI: 10.1039/b905621a
|View full text |Cite
|
Sign up to set email alerts
|

New photomagnetic cyanido-bridged CuII–MoIV oligonuclear complexes: slight modification of the blocking ligands induces different structures

Abstract: A pentanuclear complex, [Mo(CN)8{CuL1}2{CuL1(H2O)}2].6H2O 1, and a decanuclear one, [Mo(CN)8{CuL2}3{CuL2(H2O)}]2.10H2O 2, have been obtained following the building-block approach (HL1 and HL2 are tridentate Schiff bases obtained by reacting salicylaldehyde with 2-aminomethyl-pyridine and 2-aminoethyl-pyridine, respectively). Both compounds present reversible photo-induced magnetic properties interpreted as a MoIV-CuII charge transfer. Compound 2 exhibits a lower efficiency of this metal-metal charge transfer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…The photomagnetic effect in discrete systems containing Schiff base ligands was reported for pentanuclear Cu4Mo and decanuclear Cu8Mo2 molecules constructed with the Schiff base N2O ligands structurally similar to L1 ( Fig.1) 16 . The interesting case of pentanuclear Cu4Mo molecule of star topology revealed the photomagnetic effect characterised by the 22% increase of magnetic susceptibility upon irradiation with the 488 nm light.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The photomagnetic effect in discrete systems containing Schiff base ligands was reported for pentanuclear Cu4Mo and decanuclear Cu8Mo2 molecules constructed with the Schiff base N2O ligands structurally similar to L1 ( Fig.1) 16 . The interesting case of pentanuclear Cu4Mo molecule of star topology revealed the photomagnetic effect characterised by the 22% increase of magnetic susceptibility upon irradiation with the 488 nm light.…”
Section: Introductionmentioning
confidence: 74%
“…The photoconversion ratio for both systems are not high, presumably due to the surface character of the photomagnetic effect and, presumably, due to electron density withdrawal by the Schiff base ligands. However, the photoconversion reported in the analogous systems with Schiff base ligands are also relatively low 16 . The detailed analysis of the photomagnetic data allows the calculation of the coupling constant in the photogenerated metastable states as well as to establish the magnetostructural correlations.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies of the photoactive systems involving [Mo IV (CN) 8 ] 4− suggested metal‐to‐metal charge transfer (MMCT) and/or involvement of metal‐to‐ligand charge transfer (MLCT) as the possible sources of the photomagnetic effect in tetravalent octacyanidometalate‐based systems. In the present study, involvement of MMCT and MLCT seems unlikely because of a lack of strong CT absorption bands in the 400–800 nm range and the fact that irradiation experiments were done deliberately using 436 nm light (that is, at the lowest d – d transitions of the octacyanidometalate(IV) moiety).…”
Section: Figurementioning
confidence: 99%
“…A similar mechanism is used to explain the photoinduced magnetic properties of the following 0D oligonuclear assemblies: pentanuclear [Mo(CN) 8 {CuL 8 } 2 {CuL 8 (H 2 O)} 2 ] · 6H 2 O, decanuclear [Mo(CN) 8 {CuL 9 } 3 {CuL 9 (H 2 O)}] 2 · 10H 2 O50 and heptanuclear [Mo(CN) 2 (CN‐Cutren) 6 ](ClO 4 ) 8 · 4.5H 2 O 51. For the last system, detailed theoretical and kinetic models have been developed, by taking into account the contribution of the excited states of the molybdenum ion in the photomagnetic process 146148…”
Section: Functionalitymentioning
confidence: 99%